Assessment of nutritional risk in elderly adults of a senior residence – a case study - Pereira, Diana (2022)
Elderly adults have reduced appetite and energy expenditure, and possible malnutrition is related to the decline in biological and physiological functions, as well as its consequences. The aim of this study was to assess the nutritional status and malnutrition risk in elderly adults living in a senior residence. A cross-sectional observational analysis was carried out between February and March 2019 in a private senior residence in which the complete Mini Nutritional Assessment (MNA) was applied. It was observed that of the total of 45 participants, 5 individuals had a normal nutritional status, 18 had malnutrition and 22 were at risk. Malnutrition was related to a decrease in intake in the last 3 months (p=0.015) or to the fact that they experienced some type of psychological stress or acute illness in the same period (p=0.023). A higher incidence of malnutrition was also found in bedridden individuals or those in wheelchairs (p<0.001), as well as in patients with severe dementia (p=0.010), with the presence of skin lesions or bedsores (p=0.006), weight loss in the previous 3 months (p=0.003), and decreased fluid consumption (p=0.017). In conclusion, in this residence we verified that the malnutrition and malnutrition risk values are high, highlighting the need for nutritional intervention.